Design a device to detect unauthorized tapping of service cable - Mohd Zulhisham Mohd Radzi (Universiti Malaysia Perlis, 2009)
Stealing of electricity is one of the major problems that power distributors and suppliers face since it directly affects in reducing their annual turnover. Such consumers and their incorrect electrical systems should be properly recognized before taking any legal action against them. Illegal tapping of service cable before the electricity meter is the most common method. But identification becomes very difficult when all those cables are invisible to the investigator. At the same time, many mechanisms and circuitries are also deployed simultaneously to prevent being discovered. Unauthorized Tapping Detector will give clues whether the cable is tapped or not and where to investigate further. This device use a square wave generator to send a signal into the cable and reflected wave due to the tapping or cable end will determine whether the cable is being tapped or not. The reflection wave also shows the distance of tapping based on time for the wave to reflect.